CMS - Intelligent Machine Translation with Adaptation and AI - Amin, Ruhul; Mandapuram, Mounika (ABC Journal of Advanced Research, 2021)
Machine translation, an emerging breakthrough, has changed translation. Dictionary-based machine translation, computer-aided translation, and neural machine translation with AI as its fundamental technology have progressed. However, NMT with AI has advanced machine translation. Many translation concerns still need to be solved. Language changes with context and dialect. Artificial intelligence will enable systems with adaptive algorithms to collaborate with humans to translate content more efficiently and well. The human translation should be revised, according to some. All in all, human progress fixes faults. Neural networks in machine translation ensure that adaptive frameworks can interpret like human translators. AI still needs help with language training and translation. Given the diversity of linguistic patterns and civilizations, they address clever machines; even with AI, handling human productivity seems unlikely. Machine translation is an important NLP topic that uses computers and adaptive systems to understand standard dialects. Neural machine translation (NMT) has become the standard in real-world MT frameworks. We begin this study with a broad assessment of NMT strategies and discuss architecture, decoding, and data analysis to improve content translation. We then summarize the most helpful expert resources and tools. We conclude with a discussion of future paths.